Browning response of fresh-cut apples of different cultivars to cold gas plasma treatment. (May 2019) - Tappi, Silvia; Ragni, Luigi; Tylewicz, Urszula; Romani, Santina; Ramazzina, Ileana; Rocculi, Pietro
Abstract: The present work aims to study the effects of cold gas plasma on some quality parameters of apple slices belonging to four different cultivars (Pink Lady®, Fuji, Red Delicious and Modì®), with particular attention to polyphenoloxidase (PPO) inhibition and related changes in colour and visual quality. Upon plasma exposure a noticeable reduction of superficial browning was observed in all cultivars but not always proportionally to treatment time; the effect on PPO activity was very variable and not correlated to the effect on enzymatic browning. Textural parameters were affected by plasma treatments only in Red Delicious apples. Generally, the response of the tissue to the treatments was variable according to the cultivar considered. The results obtained in this study indicate the necessity of further investigation about consequences of plasma treatment on specific tissue physiology in order to choose the better treatment parameters, optimizing its effect for the specific final product. Industrial relevance: The application on cold plasma to minimally processed fruit and vegetable has shown a good potential for enzymatic browning inhibition making it an interesting alternative to traditional dipping methods. Nevertheless, the effect on the tissue to the exposure to plasma active particles is not fully known yet. For the industrial application of the treatment, the response for example of different cultivars to the treatment is of high importance, in the first place for the selection of the more appropriate raw material but also to eventually adapt the process parameters to the specificity of the matrix. Highlights: Fresh-cut apple of different cultivar was subjected to cold gas plasma treatment. Generally enzymatic browning was inhibited not proportionally to treatment time. Effect on PPO was variable and not consistent with enzymatic browning inhibition. The effect of cold gas plasma treatment is strictly cultivar dependent.